Neonatal Infection Due to SARS-CoV-2: An Epidemiological Study in Spain - Fernández Colomer, Belén; Sánchez-Luna, Manuel; de Alba Romero, Concepción; Alarcón, Ana; Baña Souto, Ana; Camba Longueira, Fátima; Cernada, María; Galve Pradell, Zenaida; González López, María; López Herrera, M. Cruz; Ribes Bautista, Carmen; Sánchez García, Laura; et al. (Frontiers in Pediatrics, 2020)
Objective: Coronavirus disease 2019 (COVID-19) cases caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continue to increase worldwide. Although some data from pediatric series are available, more evidence is required, especially in neonates, a group with specific characteristics that deserve special attention. This study aimed to describe general and clinical characteristics, management, and treatment of postnatal-acquired (community and nosocomial/hospital-acquired) COVID-19 neonatal cases in Spain. Methods: This was a national prospective epidemiological study that included cases from a National Registry supported by the Spanish Society of Neonatology. Neonates with postnatal SARS-CoV-2 infection were included in this study. General data and infection-related information (mode and source of transmission, age at diagnosis, clinical manifestations, need for hospitalization, admission unit, treatment administered, and complementary studies performed, hospital stay associated with the infection) were collected. Results: A total of 40 cases, 26 community-acquired and 14 nosocomial were registered. Ten were preterm newborns (2 community-acquired and 8 nosocomial COVID-19 cases). Mothers (in both groups) and healthcare workers (in nosocomial cases) were the main source of infection. Hospital admission was required in 22 community-acquired cases [18 admitted to the neonatal intermediate care unit (NIMCU) and 4 to the neonatal intensive care unit (NICU)]. Among nosocomial COVID-19 cases (n = 14), previously admitted for other reasons, 4 were admitted to the NIMCU and 10 to the NICU. Ten asymptomatic patients were registered (5 in each group). In the remaining cases, clinical manifestations were generally mild in both groups, including upper respiratory airways infection, febrile syndrome or acute gastroenteritis with good overall health. In both groups, most severe cases occurred in preterm neonates or neonates with concomitant pathologies. Most of the cases did not require respiratory support. Hydroxychloroquine was administered to 4 patients in the community-acquired group and to 2 patients in the nosocomial group. Follow-up after hospital discharge was performed in most patients. Conclusions: This is the largest series of COVID-19 neonatal cases in Spain published to date. Although clinical manifestations were generally mild, prevention, treatment, and management in this group are essential.